2006
DOI: 10.1676/1559-4491(2006)118[0023:neolpi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Ecology of Lesser Prairie-Chickens in Sand Sagebrush Prairie of Southwestern Kansas

Abstract: â€" Despite the fact that the Lesser Prairie-Chicken ( Tympanuchus pallidicinctus) is a species of conservation concern, little is known about its nesting ecology, particularly in sand sagebrush (.Artemisia filifolia) habitats. To find and monitor nests, we captured and equipped 227 female Lesser Prairie-Chickens with transmitters (87 yearlings, 1 17 adults, and 23 of unknown age) from 1997 to 2002 in southwestern Kansas. Apparent nest success was similar for yearlings (31%, n = 74) and adults (27%, n = 97) bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 19 publications
8
46
1
Order By: Relevance
“…In Kansas, nest sites were located further from utility lines, buildings, and improved roads than expected at random (Pitman et al 2006). Pruett et al (2009) found few Lesser Prairie-Chicken nests within 2 km of a power line in an Oklahoma study and only one Greater Prairie-Chicken nest within 2 km of the power line.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In Kansas, nest sites were located further from utility lines, buildings, and improved roads than expected at random (Pitman et al 2006). Pruett et al (2009) found few Lesser Prairie-Chicken nests within 2 km of a power line in an Oklahoma study and only one Greater Prairie-Chicken nest within 2 km of the power line.…”
Section: Discussionmentioning
confidence: 86%
“…Including state as a predictor did not greatly alter model results, and its importance was likely partly driven by sampling bias. These results are not surprising because Lesser Prairie-Chickens conduct most of their daily activities and complete their life cycle within 1.5 km of known leks (Pitman et al 2006, Boal and Pirius 2012, Grisham et al 2014. Therefore, lek suitability should increase in landscapes that contain high amounts of vegetation classes known to be used by Lesser Prairie-Chickens, i.e., shrubland or grassland systems, for other life stages such as those described by Hagen et al (2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We determined nest locations of VHF radio-tagged females by approaching the female via homing when their approximate locations remained unchanged for !3 days (Pitman et al 2006). For females with PTTs, we waited until GPS locations indicated that the female had begun incubation (when downloaded data indicated the female was stationary for !3 days) and used the GPS locations to locate the nest.…”
Section: Nest Locationmentioning
confidence: 97%
“…Endangered Species Act (U.S. Fish and Wildlife Service 2016), and attention to habitat management and conservation, evidence suggests that Lesser Prairie-Chicken populations have not recovered (McDonald et al 2015). Therefore, understanding the role of environmental stressors on nest survival may identify fine-scale interactions between nest vegetation and microclimate that have not been incorporated into previous assessments of nest ecology (Pitman et al 2006, Davis 2009, Fritts et al 2016) and thus improve conservation actions for the species.…”
Section: Introductionmentioning
confidence: 99%